Series of Photovoltaic Converters Based on Semiconductors with Intrinsic Photoconductivity - R. I. Vorobey; O. K. Gusev; A. L. Zharin; K. U. Pantsialeyeu; A. I. Svistun; A. K. Tyavlovsky; K. L. Tyavlovsky; L. I. Shadurskaya (Приборы и методы измерений, 2021)
One of the ways to solve multiple problems of optical diagnostics is to use photovoltaic converters based on semiconductors with intrinsic photoconductivity slightly doped with deep impurities which form several energy levels with different charge states within the semiconductor′s bandgap. Peculiarities of physical processes of recharging these levels make it possible to construct photodetectors with different functionality based on a range of simple device structures.The aim of this work is to analyze peculiarities of conversion characteristics of single-element photovoltaic converters based on semiconductors with intrinsic photoconductivity, to systematize their properties and to represent structures of photovoltaic convertors as a device structures suitable for implementation in measurement transducers of optical diagnostics systems.Based on the analysis of the characteristics of the conversion characteristics of single-element photovoltaic converters based on semiconductors with intrinsic photoconductivity and the requirements for their design, a dash series of photovoltaic converters was developed for use in the measuring transducers of optical diagnostics systems. The possibility of constructing functional measuring transducers for multiparameter measurements of optical signals is shown.